Improving the Knowledge and Skills Chair Pose in the Problem of Symphysis Pubis Dysfunction Using Demonstrations in Pregnancy - Shinta Alifiana Rahmawati; Suhariyati Suhariyati (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Pregnancy can result in changes in the pregnant woman, both physical and psychological cause complaints during pregnancy. At the end of pregnancy, one of the complaints felt by the mother is Symphysis Pubic Dysfunction (SPD). The aim of this research is to determine the effectiveness of health education using the demonstration method on knowledge and skills about chair pose on SPD problems for pregnant women. The research method used a quasi-experimental design with a one-group pre-posttest design. The research sample was 60 second and third trimester pregnant women using purposive sampling. The independent variable in this research was health education with the demonstration method, while the dependent variable includes knowledge and skills about chair pose for overcoming SPD problems. Data collection used questionnaire and checklist sheets. Data analysis used the Wilcoxon test. The results showed that there were significant differences in knowledge (43.75+20.17 vs. 78.75+14.74) and skills (43.33+20.71 vs. 80.00+15.28) regarding chair pose on SPD problems in third trimester pregnant women between pre-test and post-test (p0.05). Health education with an effectively demonstration method increased chair pose knowledge and skills in pregnant women's SPD problems. Increasing the knowledge and skills of pregnant women is very important, because pregnant women are a vulnerable group. The demonstration method can be applied by health workers to increase the knowledge and skills of pregnant women during pregnancy. Furthermore, researchers can increase the number of research participants to obtain more varied research results.Â